Genetic diversity of recombinant inbred lines of Phaseolus vulgaris L. - dos Santos Gomes Oliveira, Lidiane; Pin Dalvi, Leandro; Cruz de Souza, Lucimara; Aleixo da Silva, Josimar; Bastos Soares, Tais Cristina (Revista Ciência Agronômica, 2021)
Common bean is the most accessible protein source to the population and daily consumed. Studies using both morphoagronomic markers and molecular markers have been used in bean breeding programs. This work aimed to study the diversity of 22 recombinant inbred lines and, their progenitors with the aid of SSR markers. The crossing occurred in a greenhouse, between the cultivar BRS Agreste and black-01 line. The characters that showed polymorphism were evaluated: presence of anthocyanin, number of days after germination, days for flowering, wing color, standard color, seed color, tegument color, seed brightness, commercial group. The dissimilarity values ranged from 0 to 8.5; organizing the lines into three distinct groups for morphoagronomic data. In the molecular analyzes, 11 primers were monomorphic and 7 were polymorphic. The dissimilarity values for molecular analysis ranged from 0 to 0.8; with an average of 0.57. The content of polymorphic information ranged from 0.81 to 0.87. Besides the markers efficiency used in this study, they are associated to important characteristics for common bean. Joint analysis of the data presented dissimilarity values ranging from 0.0 to 12.5; with an average of 6.89; forming three groups. The joint analysis of morphoagronomic and molecular data was efficient to characterize and distinguish inbred lines. The molecular markers used were suitable to the present study. The lines 18 and 19 can be considered duplicate because in all analyzes they remained together.